KETAHANAN WATERMARKING TERHADAP SERANGAN KOMPRESI JPEG - Sugiharto, Aris; Wibawa, Helmie Arif (MATEMATIKA, 2005)
Watermarking is one of the methods that proposed to protected digital data from illegally copy.Â  A lot of technic to destroy watermarking that inserted to digital data, one of them are JPEG compression. In this research will be focus as far JPEG compression can influence watermarking integrated especially at similarity test before and after digital data have JPEG compression attact. Â